Effects of Vaccination Against Influenza, Pertussis, and COVID-19 on Human Milk Antibodies: Current Evidence and Implications for Health Equity - Hunagund, Soumya; Golan, Yarden; Asiodu, Ifeyinwa V.; Prahl, Mary; Gaw, Stephanie L. (Frontiers in Immunology, 2022)
Human milk contains three antibody classes that confer mucosal immunity to the breastfed infant: secretory IgA (SIgA), secretory IgM (SIgM), and IgG. Influenza and pertussis vaccines administered during pregnancy induce pathogen specific SIgA and IgG responses in human milk that have been shown to protect the breastfed infant from these respiratory illnesses. In addition, mRNA vaccines against the SARS-CoV-2 virus administered during pregnancy and lactation induce anti-SARS-CoV-2 IgG and IgA responses in human milk. This review summarizes the immunologic benefits of influenza, pertussis, and COVID-19 vaccines conferred by human milk. Additionally, future research direction in human milk immunity and public health needs to improve lactational support are discussed.